2016
DOI: 10.1177/1359105315571776
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral reactivity to acute stress among Black and White women with type 2 diabetes: The roles of income and racial discrimination

Abstract: This study investigated relationships of income and self-reported racial discrimination to diabetes health behaviors following an acute stressor. A total of 77 diabetic women (51% Black, 49% White) completed a laboratory public speaking stressor. That evening, participants reported same-day eating, alcohol consumption, and medication adherence; physical activity was measured with actigraphy, and the next morning participants reported sleep quality. Measures were repeated on a counterbalanced control day. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Moreover, negative psychosocial factors are associated with worse diabetes outcomes including glycemic control, long-term complications, and premature mortality (see [15] for a review of psychosocial factors among minorities with diabetes). Such associations may be direct, via elevations in stress hormones including cortisol [16] or indirect by compromising self-care behaviors, [17]. Thus, addressing the psychological wellbeing of minorities with diabetes is paramount.…”
Section: 3 Psychosocial Distress In Diabetesmentioning
confidence: 99%
“…Moreover, negative psychosocial factors are associated with worse diabetes outcomes including glycemic control, long-term complications, and premature mortality (see [15] for a review of psychosocial factors among minorities with diabetes). Such associations may be direct, via elevations in stress hormones including cortisol [16] or indirect by compromising self-care behaviors, [17]. Thus, addressing the psychological wellbeing of minorities with diabetes is paramount.…”
Section: 3 Psychosocial Distress In Diabetesmentioning
confidence: 99%
“…Were the outcome measures (dependent variables) clearly defined, valid, reliable, and implemented consistently across all study participants? Self-report sleep satisfaction was reported in 14 studies [31,33,34,[38][39][40][41][42][43][44][45][46][47][48][49][50]. A variety of measures were used across studies: the Pittsburgh Sleep Quality Index (PSQI) Global Score (n = 3) [41,44,50], the Berlin Sleep Questionnaire (n = 1) [34], the Sleep Index for Midlife Women (n = 1) [42], and the Caring for End Stage Renal Disease Health Experience Questionnaire sleep scale (n = 1) [31].…”
Section: Quality Appraisalmentioning
confidence: 99%
“…20 Finally, evidence suggests that across these 3 neighborhood factors of discrimination, crime, and violence, all 3 may also influence diabetes self-care behaviors and HbA1c through exposure to chronic stress. 21…”
Section: Purposementioning
confidence: 99%
“…20 Finally, evidence suggests that across these 3 neighborhood factors of discrimination, crime, and violence, all 3 may also influence diabetes self-care behaviors and HbA1c through exposure to chronic stress. 21 Stress is one of the major hypothesized mechanisms for why neighborhood factors affect health outcomes. 22 Stress, both acute and chronic, are shown to have negative effects on overall health via physiological and psychosocial pathways 22,23 and confers significant risk for developing diabetes.…”
Section: Purposementioning
confidence: 99%